Analisis Blibliometrik PSAK 110 Mengenai Sukuk Pada Instrumen Keuangan Syariah Menggunakan Vosviewer - Tri Dessy Fadillah; Dhea Silvia Nandita; Nirwana Arsyani Zebua; Muhammad Habib Ramadhan; Hastuti Olivia (TIN: Terapan Informatika Nusantara, 2023)
Financial instruments issued in accordance with sharia principles, provide legal certainty, are transparent and accountable. One form of sharia financial instrument that has been widely issued by both corporations and the state is securities based on sharia principles. In Indonesia, the Islamic financial instrument market, especially sukuk, is growing rapidly. This study aims to provide an overview of the existing sukuk in Indonesia by utilizing bibliometric analysis to assess the performance of scientific articles as well as to provide an overview of the advantages that are considered competitive superior products in sharia-based bonds. The research data is metadata extracted from the Google Scholar database from 2019-2023. All information is exported to a Research Information Systems (RIS) format for analysis using the VOSViewer software. The number of metadata documents collected was 997 articles. The results of the analysis show that investigating the relationship between the topics of sukuk and the Indonesian stock exchange, Islamic financial institutions, income, determinants, country, sukuk market, finance are the dominant topics ahead of 2021. Research on sukuk has broad potential and opportunities including topics. Government securities, sharia bonds, stocks